Learning to read between primers: civility, civilization and civism through the lenses of schoolbooks (Educação e Pesquisa, 2004)
The present essay seeks to identify the social locus occupied by the literacy primer in the customs and practices of the history of modern primary schooling. The purpose of the study is to examine the intermingling between the schoolbook and primary school practices through the analytical cleavage of the field of History of Education. Direction, constriction, control and confrontation, the school manual for teaching literacy proposes to highlight the context of literacy as an alternative to the orality of the world of the child. Under such premise, this work investigates the didactic production of a mid-19th century Portuguese intellectual named Francisco Júlio Caldas Aulete, more specifically his Cartilha Nacional. That literacy primer proposed a teaching that was, at one and the same time, simultaneous (since all pupils should be taught together and indistinctly, as if they were one), founded on the parallel learning of reading and writing, and explicitly against the practice of spelling - a feature that brought his proposal close to the path later characterized as the analytical method of teaching literacy. Finally, one can understand that the study by the Cartilha Nacional - despite its topical character - points to socio-historical aspects of great relevance, given that one can find in that schoolbook a clear blueprint for a country: civility, civism and civilization were the motto that directed the proposal for teaching in the initial rite of primary school.